Answered

At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

2x -y=-1
3x-2y=1
elimination somebody do this for me


Sagot :

-2(2x-y)=-1
3x-2y=1

-4x+2y=2
3x-2y=1

-x=3 (x=-3)
(-3,__)

2(-3)-y=-1
-6-y=-1
-y=-1+6
-y=5
y=-5
so..(-3,-5)
  

logo88
2x-y=-1  (1)
3x-2y=1  (2)
(1) * 2--> 4x-2y=-2   (3)
(3) - (2)
x= -3

sub x= -3 into (1)
2(-3)-y=-1
-6-y=-1
-y=5
y= -5